Knowledge, attitude, and practice toward genetic testing in breast cancer patients in China - Xin Ye; Ting Xu; Jun Cao; Gang Li; Ming Zhuang; Guangfu Hu; Hongliang Chen; Min Wang; Jie Wang (PLoS ONE, 2025)
Genetic testing is widely recommended in the diagnosis and management of breast cancer. This study aimed to investigate the knowledge, attitude, and practice (KAP) toward genetic testing in Chinese patients with breast cancer. This multicenter cross-sectional study enrolled breast cancer patients in seven public hospitals in Shanghai, China, between November 2022 and January 2023. A self-administered web-based questionnaire was used to collect the participants’ demographic information and their KAP regarding genetic testing. A total of 592 valid questionnaires were collected in this study; 145 (24.49%) patients underwent genetic testing, and 20.61% of the patients never learned about genetic testing. The knowledge, attitude, and practice scores were 4.59 ± 4.49 (22.95%, possible range: 0–20), 16.72 ± 2.92 (83.60%, possible range: 0–20), and 23.67 ± 5.18 (73.97%, possible range: 0–32), respectively. Multivariable logistic regression showed that knowledge (OR = 1.21, 95%CI: 1.51–1.28, P < 0.001), attitude (OR = 1.10, 95%CI: 1.01–1.19, P = 0.027), Jiangsu Province (OR = 0.40, 95%CI: 0.19–0.84, P = 0.016), monthly income of 5000–10,000 CNY (OR = 0.46, 95%CI: 0.25–0.86, P = 0.015), disease duration of 5–10 years (OR = 0.50, 95%CI: 0.27–0.94, P = 0.030) and disease duration of ≥ 10 years (OR = 0.26, 95%CI: 0.11–0.60, P = 0.002), triple-negative subtype (OR = 3.45, 95%CI: 1.51–7.85, P = 0.003) were independently associated with patients’ behavior of undergoing genetic testing. The structural equation modeling showed that knowledge directly positively influenced attitude (β = 0.343, P < 0.001), while attitude directly positively influenced practice (β = 0.942, P < 0.001). Chinese patients with breast cancer demonstrated poor knowledge, positive attitude, and suboptimal practice toward genetic testing. More education and counseling on genetic testing for patients are necessary.